1997
DOI: 10.1128/jb.179.11.3458-3469.1997
|View full text |Cite
|
Sign up to set email alerts
|

Maximization of transcription of the serC (pdxF)-aroA multifunctional operon by antagonistic effects of the cyclic AMP (cAMP) receptor protein-cAMP complex and Lrp global regulators of Escherichia coli K-12

Abstract: The arrangement of the Escherichia coli serC (pdxF) and aroA genes into a cotranscribed multifunctional operon allows coregulation of two enzymes required for the biosynthesis of L-serine, pyridoxal 5-phosphate, chorismate, and the aromatic amino acids and vitamins. RNase T 2 protection assays revealed two major transcripts that were initiated from a promoter upstream from serC (pdxF). Between 80 to 90% of serC (pdxF) transcripts were present in single-gene mRNA molecules that likely arose by Rho-independent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 57 publications
1
21
0
Order By: Relevance
“…␤-Galactosidase specific activities in exponentially growing (50K) or stationary-phase (24-h) cultures were measured with a plate reader as described before (43). Differential rates of ␤-galactosidase synthesis were determined from plots of total ␤-galactosidase activity per milliliter of culture per reaction time graphed against cell mass (A 600 ) as described previously (43).…”
mentioning
confidence: 99%
“…␤-Galactosidase specific activities in exponentially growing (50K) or stationary-phase (24-h) cultures were measured with a plate reader as described before (43). Differential rates of ␤-galactosidase synthesis were determined from plots of total ␤-galactosidase activity per milliliter of culture per reaction time graphed against cell mass (A 600 ) as described previously (43).…”
mentioning
confidence: 99%
“…To fully understand the control and integration of PLP biosynthesis, we have been determining whether the individual PLP biosynthetic genes are subject to forms of metabolic regulation. Previously, we reported that the serC (pdxF) gene is positively regulated by the Lrp protein and negatively regulated by the cyclic AMP receptor protein (43). Here we report that transcription of the pdxA and pdxB genes is positively growth rate regulated by two different mechanisms.…”
mentioning
confidence: 61%
“…Moreover, other PLP biosynthetic genes do not follow the pattern of positive growth rate regulation reported here for pdxA and pdxB. For example, expression of the serC (pdxF)-encoded transaminase, which acts between PdxB and PdxA in the de novo PLP pathway (40,43), is minimal in rich LB medium and maximal in minimal salts-glucose medium due to opposing positive and negative controls exerted by the Lrp and cyclic AMP receptor proteins, respectively (T.-K. Man and M. E. Winkler, unpublished results) (43). However, the regulation of the SerC (PdxF) transaminase may have been strongly set by its central role in serine biosynthesis (63).…”
Section: Discussionmentioning
confidence: 99%
“…The general idea predicts that all isoprenoid biosynthetic genes are in multigene operons with essential distal genes. This prediction has not yet been tested, but such mixedfunction operons are known (17,19,34).…”
Section: Discussionmentioning
confidence: 99%